1994
DOI: 10.1007/bf00891781
|View full text |Cite
|
Sign up to set email alerts
|

Peer versus staff tutoring in problem-based learning

Abstract: Abstract. Effects of student versus stafftutoring on student learning in a problem-based, health sciences curriculum were studied. Academic achievement of 334 tutorial groups guided by stafftutors was compared with achievement of 400 groups guided by student tutors. In addition, students rated their tutor's performance on four behaviors considered critical to facilitating student learning. Overall, students guided by a staff tutor achieved somewhat better. In terms of practical significance, the difference was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 9 publications
2
62
0
Order By: Relevance
“…For example, a common weakness of the studies included was failure to blind those grading the academic performance when ratings were subjective. Of the studies that used either subjective methods 14,15,17,25,26,29,32,34 or failed to describe assessment methods, 16,20,21,23,24,27,30,31 only 1 group of investigators blinded the graders. 15 Another potential weakness of the studies under review is nonrandom exclusion of participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a common weakness of the studies included was failure to blind those grading the academic performance when ratings were subjective. Of the studies that used either subjective methods 14,15,17,25,26,29,32,34 or failed to describe assessment methods, 16,20,21,23,24,27,30,31 only 1 group of investigators blinded the graders. 15 Another potential weakness of the studies under review is nonrandom exclusion of participants.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies did not detect a difference between the performance of students tutored by peers versus students tutored by faculty or staff members, 14,15,17,28,29 4 studies found mixed results, 30,[32][33][34] and 1 study found the performance of peer-tutored students to be better. 26 Validity and reliability information for each study's measure of student achievement or performance was evaluated. Only 4 of the 20 studies provided evidence of the reliability of the assessment method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of recommendations for optimal tutor characteristics within PBL literature is often confusing, with some recommendations being closely overlapped while others offer direct contradictions. For example, some researchers recommend that tutors be content experts or faculty with facilitation training (Barrows, 1996;Bochner et al, 2002;Gilkison, 2003;Schmidt & Moust, 1995;Schmidt, Van Der Arend, Moust, Kokx, & Boon, 1993;Schmidt et al, 1994). An early effort that characterizes the impacts of tutor expertise in relation to faculty direction of students (Albanese & Mitchell, 1993) found that expert tutors provide less engagement for student-directed discussion and learning (Davis, Nairn, Paine, Anderson, & Oh, 1992;Silver & Wilkerson, 1991) and were more likely to intervene in student-directed discussion (De Volder, 1982).…”
Section: Tutor Content Expertisementioning
confidence: 99%
“…The tutor provides a student-centered learning environment by promoting self-directed learning, the integration of previous knowledge, interaction, and guiding the learning process (Chan, 2008;De Grave, Dolmans, & van der Vleuten, 1999;Hmelo-Silver & Barrows, 2006). Within existing PBL literature, some researchers promote tutors as requiring content expertise (Barrows, 1996;Hmelo-Silver & Barrows, 2006;Dede, 2003), while some argue content experts are not necessary (Barrows, 1986(Barrows, , 1998Swanson, Stalenhoef-Halling, & van der Vleuten, 1990), and still others claim that content experts and content novices should be used at different stages of PBL instruction (Schmidt, Van Der Arend, Kokx, & Boon, 1994). There may even be an interaction between training and background, with evidence that training is particularly important for tutors with content expertise (De Volder, 1982;Silver & Wilkerson, 1991).…”
Section: Introductionmentioning
confidence: 99%